Combined effects of nitrate concentration and illumination conditions on the growth of microalga Haematococcus pluvialis - Hong, Dang Diem; Ngoc Mai, Dinh Thi; Lam, Bui Dinh; Tam, Luu Thi; Thu Thuy, Nguyen Thi; Ha, Nguyen Cam; Thom, Le Thi; Hoang, Dinh Duc; Anh, Hoang Lan; Hoai Thu, Ngo Thi (Academia Journal of Biology, 2013)
Astaxanthin (3, 3’- dihydroxy β, β carotene - 4,4 - dione) is a biologically active pigment with applications in aquaculture, nutraceutical, pharmaceutical, and food industries. Although astaxanthin can be synthesized by plants, bacteria, a few fungi, and green algae, the amounts produced by the green microalga Haematococcus pluvialis surpass any other reported source. However, this microalga is not easily commercially cultivated because of the low cell growth rate, sensitivity of the cells to high hydrodynamic stress and changes in cell morphology under various environmental conditions. This work aimed to investigate the combined effects of nitrate concentration and illumination conditions on the cultivation of vegetative cells Haematococcus pluvialis to achieve high cell density. A 25% increase in the maximum cell density was observed as the NaNO3 concentration in RM medium increased from 300 to 1200 mg/l. In addition, the obtained results also shown that the perfusion culture process plus increasing of nitrate concentration and controlling illumination conditions is an effective strategy for high-density cultivation of H. pluvialis. The maximum cell density of 3.2 × 106 cells/ml on the 22nd day yielded from a culture illuminated with 16 h light/ 8 h dark cycle in which time of illumination by flourescent lamps is 10 hours and time of combined illumination by fluorescent lamps and UV lamps is 6 hours. The highest cell density of the culture illuminated with fluorescent lamps 2.5 klux for 12 h per day and the culture illuminated with fluorescent lamps 4.3 klux for 16 h per day reached 0.9 × 106 cells/ml and 1.8 × 106 cells/ml after 19 days of cultivation, respectively.